2009
DOI: 10.1007/s12565-008-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical aspects of the male reproductive system in the bonnet monkey (Macaca radiata)

Abstract: The normal anatomy of the male reproductive system in Macaca radiata is presented here. The external genitalia consist of a triangular button-shaped glans penis. The corpus cavernosum, and spongiosum form the vascular component of the penis and the baculum or os penis forms the non-vascular erectile component. The baculum is one of the longest in the genus macaques. The scrotal sac is non-pigmented, slightly pendulous, with scattered hairs, faintly corrugated, and does not reach the ischial callosities in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 31 publications
4
16
1
Order By: Relevance
“…The bonnet monkey is a tropical inhabitant of the Indian subcontinent sharing reasonable similarity with human in terms of testis and its duct system. The shamoperated control showed normal histological testes and epididymides architecture and almost similar to normal monkey data reported earlier [Prakash et al 2009] and ruled out any iatrogenic effect. After vasectomy, the testes and epididymides underwent gross alterations in both short-term and long-term animals.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The bonnet monkey is a tropical inhabitant of the Indian subcontinent sharing reasonable similarity with human in terms of testis and its duct system. The shamoperated control showed normal histological testes and epididymides architecture and almost similar to normal monkey data reported earlier [Prakash et al 2009] and ruled out any iatrogenic effect. After vasectomy, the testes and epididymides underwent gross alterations in both short-term and long-term animals.…”
Section: Discussionsupporting
confidence: 85%
“…The sham-operated control testes and epididymides had no inflammatory reaction and demonstrated normal histoarchitecture as described elsewhere [Prakash et al 2009]. …”
Section: Histopathologymentioning
confidence: 99%
“…Sections were stained with Ehrlich alum hematoxylin and eosin and observed under bright-field microscope (Nikon Corporation, Tokyo, Japan). Histomorphometric analysis was done, details of the procedure are described elsewhere [Prakash et al 2008;Prakash et al 2009]. Values are given in relative terms.…”
Section: Sperm Collection and Detection Of Anti-sperm Antibodiesmentioning
confidence: 99%
“…Prostate in Anatolian souslik is on the dorsal face of begining of urethra and as a single lobe on the ventral face of rectum (Cakır and Karatas, 2004). Prostate gland of monkey is like a cone (Prakash et al, 2009). Prostate of a fox, on the other hand, is circular and it was observed that it was in the caudal of urinary bladder as similar to dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Glans penis of fox, which is a wild animal, was observed as coming out with ostium urehtra externum. Glans penis of a monkey, on the other hand, is triangular in shape or like a button (Prakash et al, 2009). Penis of a hyena, a wild carnivore, is chisel-shaped (Cunha et al, 2014).…”
Section: Discussionmentioning
confidence: 99%